Fractal dimension of the retinal vasculature and risk of stroke : a nested case-control study - Kawasaki, Ryo; Che Azemin, Mohd Zulfaezal; Kumar, Dinesh Kant; Tan, Ava Grace; Liew, Gerald; Wong, Tien Yin; Mitchell, Paul; Wang, Jie Jin (2011)
Recent studies show associations between retinal vascular changes and small infarcts detected on brain imaging, or clinical stroke. Fractal dimension has been used as a global measure of the geometric pattern of the retinal vasculature potentially representing the complex branching pattern of the microvasculature, including the cerebral microvasculature. We have developed an automatic method to assess spectrum fractal dimension (SFD) of the retinal microvasculature using Fourier-transformed images. Two previous studies have reported cross-sectional associations between retinal fractal dimension and lacunar stroke. In this study, we aimed to examine the association between baseline SFD and stroke incidence using a case-control sample nested in the Blue Mountains Eye Study (BMES).